Pyrostegia venusta heptane extract containing saturated aliphatic hydrocarbons induces apoptosis on B16F10-Nex2 melanoma cells and displays antitumor activity in vivo - Figueiredo, Carlos R.; Matsuo, Alisson L.; Pereira, Felipe V.; Rabaca, Aline N.; Farias, Camyla F.; Girola, Natalia; Massaoka, Mariana H.; Azevedo, Ricardo A.; Scutti, Jorge A. B.; Arruda, Denise C.; Silva, Luciana P. [UNESP]; Rodrigues, Elaine G.; et al. (Medknow Publications & Media Pvt Ltd, 2014)
Background: Pyrostegia venusta (Ker. Gawl.) Miers (Bignoniacea) is a medicinal plant from the Brazilian Cerrado used to treat leucoderma and common diseases of the respiratory system. Objective: To investigate the antitumor activity of P.venusta extracts against melanoma. Materials and Methods: The cytotoxic activity and tumor induced cell death of heptane extract (HE) from P. venusta flowers was evaluated against murine melanoma B16F10-Nex2 cells in vitro and in a syngeneic model in vivo. Results: We found that HE induced apoptosis in melanoma cells by disruption of the mitochondrial membrane potential, induction of reactive oxygen species and late apoptosis evidenced by plasma membrane blebbing, cell shrinkage, chromatin condensation and DNA fragmentation, exposure of phosphatidylserine on the cell surface and activation of caspase-2,-3,-8,-9. HE was also protective against singeneyc subcutaneous melanoma HE compounds were also able to induce cell cycle arrest at G2/M phases on tumor cells. On fractionation of HE in silica gel we isolated a cytotoxic fraction that contained a mixture of saturated hydrocarbons identified by (1) H NMR and GC-MS analyses. Predominant species were octacosane (C 28 H 58 -36%) and triacontane (C 30 H 62 -13%), which individually showed significant cytotoxic activity against murine melanoma B16F10-Nex2 cells in vitro and a very promising antitumor protection against subcutaneous melanoma in vivo. Conclusion: The results suggest that the components of the heptane extract, mainly octasane and triacontane, which showed antitumor properties in experimental melanoma upon regional administration, might also be therapeutic in human cancer, such as in the mostly epidermal and slowly invasive melanomas, such as acral lentiginous melanoma, as an adjuvant treatment to surgical excision.
Keywords: Apoptosis; cytotoxicity; melanoma; Pyrostegia venusta; saturated hydrocarbons